Increasing environmental filtering of diazotrophic communities with a decade of latitudinal soil transplantation. (March 2021) - Tang, Haoqi; Zhang, Na; Ni, Haowei; Xu, Xiaofeng; Wang, Xiaoyue; Sui, Yueyu; Sun, Bo; Liang, Yuting
Abstract: Biological nitrogen fixation is an important process to reduce fertilizer application in agriculture ecosystem. However, with accelerated climate warming, it is still unknown how diazotrophs (nitrogen fixing microorganisms) succeed and assemble in long-term field-based experiment. By southward translocating arable Mollisols to a warm-temperate region for a decade to simulate changing climatic regimes, a continuous diversity decrease and structure change was observed for soil diazotrophs, accompanied by a reduction in fertilizer effect on crop productivity and quality. The RNA sequencing based on reverse transcription indicated that dominant diazotrophs were more sensitive to soil transplantation compared to relatively resistant rare taxa. Variations of dominant diazotrophs accounted significantly for the reduction of yield change (17%–20%). Co-occurrence network became more complex with soil transplantation, with increasingly competitive associations among the dominants. Warming climatic regimes acted as a strong environmental filter that increased the deterministic community assembly. Meanwhile, the dominant diazotrophs became more dispersal restricted by quantitation ecological drift, homogenizing dispersal and dispersal limitation processes in stochasticity. An integrated structural equation model further suggested that besides the directly negative effect of warming on the crop yield, the increasing competition of diazotrophic community may also link to the crop productivity and quality. Highlights: A decade soil transplantation decreased nifH abundance and diazotrophs diversity. Dominant diazotrophs were more sensitive to soil transplantation than rare taxa. Warming climatic regimes increased the deterministic community assembly.